2017
DOI: 10.5114/aoms.2016.58270
|View full text |Cite
|
Sign up to set email alerts
|

Scal atrial natriuretic peptide gene polymorphisms and their possible association with postoperative atrial fibrillation – a preliminary report

Abstract: IntroductionAtrial fibrillation (AF) is a frequently encountered complication after coronary artery bypass grafting (CABG), but its underlying mechanisms are still unclear. The natriuretic peptides have been reported as markers for predicting the occurrence of postoperative AF. This study evaluates whether the ScaI ANP gene polymorphisms predict the occurrence of postoperative AF.Material and methodsA prospective study of 203 consecutive patients with coronary artery disease undergoing elective CABG was undert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 32 publications
0
7
0
1
Order By: Relevance
“…Subsequently, 254 duplicate records were excluded. After reviewing the titles and abstracts of the documents, and further reading of the full text, 12 documents (8,11,13,(16)(17)(18)(19)(20)(21)(22)(23)(24) including 45,619 patients were finally included in the present meta-analysis (Fig. S1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, 254 duplicate records were excluded. After reviewing the titles and abstracts of the documents, and further reading of the full text, 12 documents (8,11,13,(16)(17)(18)(19)(20)(21)(22)(23)(24) including 45,619 patients were finally included in the present meta-analysis (Fig. S1).…”
Section: Resultsmentioning
confidence: 99%
“…In the present meta-analysis, the relationship of ANP gene polymorphisms with the occurrence of cardiovascular diseases was evaluated, and 12 studies were included (8,11,13,(16)(17)(18)(19)(20)(21)(22)(23)(24). The results of the analysis showed that the ANP 2238T/C polymorphism was significantly associated with the occurrence of myocardial infarction, cerebrovascular events and the composite CVE outcomes, while the ANP 2238T/C polymorphism was not associated with the risk of other cardiovascular events (e.g., atrial fibrillation or coronary artery disease).…”
Section: Discussionmentioning
confidence: 99%
“…Adding genetic factors to clinical factors in multivariate regression models helps identify new-onset atrial fibrillation [140]. Siebert et al [142] conducted a prospective study of 203 patients with coronary artery disease who underwent coronary artery bypass grafting and did not find that the Scal polymorphism in the ANP gene predicted new-onset atrial fibrillation after coro-nary artery bypass. Kertai et al [143] similarly selected coronary artery bypass graft patients and found that only SNP rs10504554, located in the LY96 intron region, was associated with a reduced risk of new-onset postoperative atrial fibrillation based on a genome-wide association study (OR 0.48, 95% CI 0.34-0.68, p = 2.9 × 10 −5 ).…”
Section: Gene Polymorphisms and New-onset Atrial Fibrillationmentioning
confidence: 99%
“…The mutation frequency is estimated to be high, perhaps as high as 14% in the general population. The mutation is associated with increased risk of myocardial infarction and stroke ( 47-50 ) but seemingly not to hypertension ( 51 , 52 ). From a pharmacological point of view, this mutation has attracted some attention.…”
Section: Geneticsmentioning
confidence: 99%